Study of carbon monoxide levels in the most traveled streets of Metropolitan Lima - Vargas Gonzales, Alejandra (2023)
This article seeks to determine the levels of carbon monoxide (CO) in the air in the busiest streets of modern Lima to which pedestrians are exposed. To measure the concentration of CO, measurements were taken five days a week at three different times of the day, considering the hours with the highest traffic congestion. Also, several factors were considered, such as traffic level, time of day, day of the week, and type of transport. The measurements were taken with a Cheffort portable CO detector, and the results were recorded continuously and in real time to identify if there is a correlation between the factors and the level of this pollutant. As a result, it was determined that there is a direct and statistically significant relationship between the level of traffic and the level of carbon monoxide. In addition, the days with the highest concentration are Fridays with an average of 38,259 ug/m3 and the area with the highest CO levels is Javier Prado Avenue with an average of 38,514 ug/m3, being this avenue, a main artery compared to Benavides Avenue. Finally, it is concluded that the levels of carbon monoxide emissions in the streets of Metropolitan Lima are around 29,789 ug/m3, which is very close to the Maximum Permissible Limits (MPL), high levels can affect the health of passersby, so it is important to take into account the factors that increase the levels of this pollutant in order to seek optimal solutions and avoid the continuous increase of carbon monoxide in the air.